Who Are the Freshmen at Highest Risk of Dropping Out of University? Psychological and Educational Implications - Chiara Buizza; Sara Bornatici; Clarissa Ferrari; Giulio Sbravati; Giuseppe Rainieri; Herald Cela; Alberto Ghilardi (MDPI AG, 2024)
It is estimated that one in three students drop out of university by the end of the first year of study. Dropping out of university has significant consequences, not only for the student but also for the university and for society as a whole. A total of 1.154 Italian freshmen were involved in this study and were divided based on their intention to dropout from university. The intention to dropout was assessed using five questions, and motivation was assessed through the Academic Motivation Scale. Differences in socio-demographic factors, extra-curriculum activities, academic characteristics, and academic motivation between freshmen with low and high dropout risks were assessed for highlighting potential intervention for limiting dropout rates. The majority of the freshmen were female, from low-income families, had attended high school, and lived out of town; the most represented field of study was health professions. The results indicate that the variables increasing the likelihood of belonging to the high dropout risk group are as follows: unsatisfactory relationships with lecturers/professors and fellow students, low income, amotivation, and extrinsic motivation. This study underlines the importance of adopting new teaching approaches that include spaces and time dedicated to fostering relationships, supporting academic success, and promoting the psychosocial well-being of students.